Decomposing the Dynamics of Regional Earnings Disparities in Israel - Michael Beenstock; Daniel Felsenstein (European Regional Science Association (ERSA), 2003)
The literature on regional growth convergence and economic disparities has tended to confound four interwoven measurement phenomena. i) mean reversion (so-called beta convergence) where richer regions move towards the average from above and poorer regions from below. ii) diminishing inequality (so called sigma convergence) where the horizontal or spatial distribution of income becomes more equal. iii) mobility, where the rank of a region in the overall distribution of income changes either upwards or downwards. iv) leveling, where the richer regions become poorer (leveling-down) or the poorer regions become richer (leveling-up). We use a new statistical methodology, which treats these four phenomena on an integrated basis. The methodology is applied to Israeli regional earnings and house price data. We find that whereas earnings are strongly sigma divergent during the 1990s, this trend is offset when regional cost of living differences are taken into consideration. In this event, regional housing markets induce convergence in similar measure to the divergence induced by regional labor earnings.
Keywords: 330